A Study of Implied Risk-Neutral Density Functions in the Norwegian Option Market - Stig Arild Syrdal (Norges Bank, 2002)
Option prices are assumed to contain unique information about how market participants assess the likelihood of different outcomes for future market prices. The main object of this study is to analyse the potential value of information contained in prices of options on the OBX index at Oslo Stock Exchange. The information is extracted using implied risk-neutral density functions. The study shows that there is a high level of uncertainty surrounding the implied density functions extracted from OBX options. Uncertainty introduced by using an average of the closing bid and ask quotation as a proxy for the option price, and the small range of actively traded strike prices, suggest that we should not place to much confidence in estimates sensitive to the tails of the implied density functions. The small range of actively traded strike prices is probably also a major reason for the differences often observed between various estimation techniques. Using information contained in OBX option prices in forecasting future market prices seems to be worthless. Some information about future volatility may be obtained, but not about the direction of future outcomes.
hdl:11250/2498655
Keywords: C10; G13; 330; implied risk-neutral density functions; option pricing; market expectations